2008
DOI: 10.1007/s10162-008-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Sparc Protein Is Required for Normal Growth of Zebrafish Otoliths

Abstract: Otoliths and the homologous otoconia in the inner ear are essential for balance. Their morphogenesis is less understood than that of other biominerals, such as bone, and only a small number of their constituent proteins have been characterized. As a novel approach to identify unknown otolith proteins, we employed shotgun proteomics to analyze crude extracts from trout and catfish otoliths. We found three proteins that had not been associated previously with otolith or otoconia formation: 'Secreted acidic cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 81 publications
5
64
0
1
Order By: Relevance
“…Non-collagenous ECM proteins such as osteonectin (OSN) and matrix Gla protein have been identified in sea bream, the goldfish Carassius auratus, zebrafish and the bluegill Lepomis macrochirus (Kang et al 2008;Lehane et al 1999;Nishimoto et al 1992;Pinto et al 2003;Redruello et al 2005;Rotllant et al 2008). Moreover, a novel lectican gene, dermacan, has been reported as being active in zebrafish dermal bone (Kang et al 2004) and bone Gla protein (osteocalcin) has been characterised in zebrafish (Danio rerio), Senegal sole (Solea senegalensis, Gavaia et al 2006) and medaka (Renn and Winkler 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Non-collagenous ECM proteins such as osteonectin (OSN) and matrix Gla protein have been identified in sea bream, the goldfish Carassius auratus, zebrafish and the bluegill Lepomis macrochirus (Kang et al 2008;Lehane et al 1999;Nishimoto et al 1992;Pinto et al 2003;Redruello et al 2005;Rotllant et al 2008). Moreover, a novel lectican gene, dermacan, has been reported as being active in zebrafish dermal bone (Kang et al 2004) and bone Gla protein (osteocalcin) has been characterised in zebrafish (Danio rerio), Senegal sole (Solea senegalensis, Gavaia et al 2006) and medaka (Renn and Winkler 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Although proteins for less than 5% of an otolith's weight, they play an important role in the morphogenesis of the microcrystalline calcium carbonate of otoliths (Kang et al 2008). Sulfur-based amino acids, such as cysteine, are in four of the five proteins found in otoliths, and these are important for the proper folding and stabilization of a protein's three-dimensional structure (R. Kollamar, SUNY Downstate Medical Center, NY, USA, pers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with zebrafish demonstrated that SPARC knockdown by morpholinos lead to defects in otic vesicles and pharyngeal cartilage, at stages after SPARC transcripts are detected (Kang et al 2008;Rotllant et al 2008). In contrast to zebrafish, SPARC is not detected in Xenopus embryos by whole mount in situ hybridization and immunohistochemistry in otic vesicles, even in stage 30 tailbud embryos (Damjanovski et al 1994), by which time distinct otic vesicles are visible in transverse sections.…”
Section: Discussionmentioning
confidence: 93%